Avaliação cardíaca de cães com cinomose - Araujo, Juliana Bornhausen Cardoso [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
A cinomose é uma relevante doença infectocontagiosa no Brasil e possui um crescente número de mortes em sua decorrência. É comprovado que esta doença causa importantes alterações histopatológicas cardíacas, porém seus efeitos sobre o sistema cardiovascular foram pouco descritos. O presente estudo teve como objetivo avaliar a atividade do vírus no coração por meio da ecocardiografia, da eletrocardiografia e da monitorização eletrocardiográfica ambulatorial, mais conhecida como método Holter.

Distemper is an important infectious disease in Brazil that unfortunately has a crescent death toll. It has been proven that the virus has important histopathologic effects over the cardiovascular system although that has been scarcely researched. The present study has the objective of evaluating the virus’s activity on the heart with the help of echocardiography, electrocardiography and Holter. The ambulatory electrocardiographic monitoring, also known as Holter exam, is an effective way of detecting cardiac arrhythmias and sometimes can help with early detection of cardiac lesions.
Cardiac evaluation of dogs with distemper
Keywords: cães; morbilivirus; cinomose; variabilidade da frequência cardíaca; holter; ecocardiografia; Canine; Morbilivirus; Heart rate variability; Holter; Echocardiography